STRATEGI PENGEMBANGAN DAKWAH DI SULAWESI SELATAN MELALUI MEDIA SOSIAL UNTUK GENERASI MILENIAL - Hidayat, Tatang; Bakri, Mu'adz; Istianah, Istianah (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
This research is motivated by da'wah development strategies that tend to neglect the millennial generation in using social media. The purpose of this research is to find out the strategy of developing da'wah in South Sulawesi through social media. This research uses a qualitative approach and literature study method. Data collection techniques come from the Qur'an, journals, books, and media. Data interpretation and data analysis techniques were combined. The results of this study show that social media is a common way for millennials to communicate with each other and obtain information. As a result, approaches to da'wah dissemination through social media should be modified to take into account the interests and nature of millennial audiences. This study also emphasizes how important interactive, inventive, and relevant information is to capture the attention of millennials.